2021
DOI: 10.1123/ijspp.2020-0065
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Lifting Lighter and Heavier Loads on Subjective Measures

Abstract: Background: Despite the progress made in the study of subjective measures in resistance training, some questions remain unanswered. Here the authors investigated if ratings of perceived exertion (RPE) can predict task failure and bar velocity across exercises and loads as a primary outcome and whether a battery of subjective measures differ as a function of the lifted loads as a secondary outcome. Methods: In this preregistered study, 20 resistance-trained subjects (50% female) first completed a 1-repetition-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 23 publications
3
32
0
Order By: Relevance
“…The internal meta-analysis echoed the results of Experiment 2 supporting that participants under predicted. These results are mostly in line with previous findings (Hackett et al, 2012(Hackett et al, , 2016Giessing et al, 2016a,b;Altoé Lemos et al, 2017;Steele et al, 2017a;Zourdos et al, 2019;Emanuel et al, 2020;Hughes et al, 2020;Mansfield et al, 2020). However, in contrast with prior research this study is the first to examine predictive ability at the sdRM/0RIR.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The internal meta-analysis echoed the results of Experiment 2 supporting that participants under predicted. These results are mostly in line with previous findings (Hackett et al, 2012(Hackett et al, , 2016Giessing et al, 2016a,b;Altoé Lemos et al, 2017;Steele et al, 2017a;Zourdos et al, 2019;Emanuel et al, 2020;Hughes et al, 2020;Mansfield et al, 2020). However, in contrast with prior research this study is the first to examine predictive ability at the sdRM/0RIR.…”
Section: Discussionsupporting
confidence: 92%
“…The overall results of these studies suggest participants generally under predict the number of repetitions they can perform to MF whether predictions are made a priori to initiation of exercise, or at varying degrees of proximity to actual MF. Improved accuracy, which has been shown with subsequent sets (Hackett et al, 2012;Emanuel et al, 2020;Mansfield et al, 2020) or heavier loads (Altoé Lemos et al, 2017;Emanuel et al, 2020;Hughes et al, 2020), would suggest proximity to MF may play a role, though accuracy may still be imperfect. Indeed, Zourdos et al (2019) found that, despite improved accuracy of predictions with closer proximity to MF, participants still under predicted when they thought they were 5, 3, and 1 repetition away from MF (difference between predicted and actual of 5.15 ± 2.92, 3.65 ± 2.46, and 2.05 ± 1.73 for 5RIR, 3RIR, and 1RIR, respectively).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations